2017
DOI: 10.1002/ecy.1879
|View full text |Cite
|
Sign up to set email alerts
|

Competition drives the response of soil microbial diversity to increased grazing by vertebrate herbivores

Abstract: Abstract. Scientists have largely neglected the effects of grazing on soil microbial communities despite their importance as drivers of ecosystem functions and services. We hypothesized that changes in soil properties resulting from grazing regulate the diversity of soil microbes by releasing/suppressing subordinate microbial taxa via competition. To test this, we examined how intensity of vertebrate herbivores influences the diversity and composition of soil bacteria and fungi at 216 soil samples from 54 site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 67 publications
(123 reference statements)
5
68
1
Order By: Relevance
“…Also, CW-VH had a positive significant relationship with organic carbon (χ 2 = 32.61; p =< 0.001), possibly because of increased amounts of litter material. We propose that this process could be related to the competitive exclusion principle; that is, increases in the abundance of some species result in decreases or even extinction of others (Eldridge et al, 2017). However, other studies showed a positive relationship with total abundance of bacterial communities, but negative with diversity of soil bacteria, at least in soils with enough carbon content .…”
Section: Cascading Effects Of Plant Species Richness and Climate Chmentioning
confidence: 84%
“…Also, CW-VH had a positive significant relationship with organic carbon (χ 2 = 32.61; p =< 0.001), possibly because of increased amounts of litter material. We propose that this process could be related to the competitive exclusion principle; that is, increases in the abundance of some species result in decreases or even extinction of others (Eldridge et al, 2017). However, other studies showed a positive relationship with total abundance of bacterial communities, but negative with diversity of soil bacteria, at least in soils with enough carbon content .…”
Section: Cascading Effects Of Plant Species Richness and Climate Chmentioning
confidence: 84%
“…Our SEM results indicate that plant cover had a strong negative effect on the diversity of bacteria and/or fungi in both Australia and England. More specifically, our results suggest that increases in percentage plant cover might lead to the exclusion of microbial species via the competition‐to‐exclusion principle (Eldridge et al ., ). In addition, unlike Australia, in England, plant leaf N content (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Other published meta‐analyses revealed that light grazing practices had no effect on soil microbial community, but heavy grazing significantly reduced the size of microbial community (Zhao et al, ). Grazing has a significant effect on the composition of soil microbial biodiversity (Chávez, Escobar, Anghinoni, de Faccio Carvalho, & Meurer, ; Eldridge et al, ), which is particularly significant in arid northwestern China. For example, in the dry steppe of the Loess Plateau, grazing exclusion for 20 years significantly increased microbial biomass in the 0‐ to 10‐cm layer compared with continuous grazing (Cheng et al, ).…”
Section: Grazing Exclusion and Soil Propertiesmentioning
confidence: 99%
“…Other published meta-analyses revealed that light grazing practices had no effect on soil microbial community, but heavy grazing significantly reduced the size of microbial community . Grazing has a significant effect on the composition of soil microbial biodiversity (Chávez, Escobar, Anghinoni, de Faccio Carvalho, & Meurer, 2011;Eldridge et al, 2017), which is particularly significant in arid northwestern…”
Section: Soil Biological Propertiesmentioning
confidence: 99%